Magnetic Perovskites Sr2FeMoO6 and La(1-x)Ca(x)MnO3: Synthesis, Fabrication and Characterization of Nanosized Powders and Thin Films - Suominen, Tanja (fi=Turun yliopisto|en=University of Turku|, 2009)
Due to font problem on the tilte field the titlte of the thesis is corrected here. The title of the thesis is: Magnetic Perovskites Sr2FeMoO6 and La(1-x)Ca(x)MnO3: Synthesis, Fabrication and Characterization of Nanosized Powders and Thin Films
Keywords: materiaalitiede